Extraction, identification and antimicrobial activity of a new furanone, grifolaone A, from Grifola frondosa. Issue 8 (17th April 2016) - He, Xiaoyun; Du, Xuezhu; Zang, Xiangyun; Dong, Lili; Gu, Zijian; Cao, Liping; Chen, Dafu; Keyhani, Nemat O.; Yao, Lindan; Qiu, Junzhi; Guan, Xiong
Abstract: A furanone (1 ), ( S )-methyl 2-(2-hydroxy-3, 4-dimethyl-5-oxo-2, 5-dihydrofuran-2-yl)acetate, was isolated from the edible mushroom Grifola frondosa . Mass spectrometry and NMR analyses were used to elucidate the structure of this compound, and its absolute configuration was determined using circular dichroism spectroscopy. Compound1 exhibited specific antifungal activity against the plant pathogens, Fusarium oxysporum, Gibberella zeae and Piricularia oryzae and the opportunistic human pathogen, Pseudallescheria boydii, resulting in minimum inhibitory concentration values of 2.5, 2.5, 1.25 and 0.15 μg/mL, respectively. In contrast, the furanone showed only weak activity towards Aspergillus spp., Candida albicans and several other fungal strains tested as well as no appreciable antibacterial activity. Abstract :